2023
DOI: 10.1158/1078-0432.ccr-23-0204
|View full text |Cite
|
Sign up to set email alerts
|

ILUSTRO: Phase II Multicohort Trial of Zolbetuximab in Patients with Advanced or Metastatic Claudin 18.2–Positive Gastric or Gastroesophageal Junction Adenocarcinoma

Samuel J. Klempner,
Keun-Wook Lee,
Kohei Shitara
et al.

Abstract: Background: Zolbetuximab, an IgG1 monoclonal antibody, binds to claudin 18.2 (CLDN18.2) and mediates tumor cell death through antibody-dependent cellular cytotoxicity and complement-dependent cytotoxicity. We sought to examine zolbetuximab combinations in CLDN18.2-positive human epidermal growth factor receptor 2–negative gastric/gastroesophageal junction (G/GEJ) adenocarcinoma. Patients and methods: This phase 2 study assessed efficacy and safety of zolbetuximab, alone or with modified FOLFOX6 (mFOLFOX6) or p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…In line with the FAST trial outcomes, a recent phase II study also demonstrated interesting ORR and PFS results for the combination of zolbetuximab and chemotherapy in CLDN18.2-positive gastric or gastroesophageal adenocarcinoma [64]. The ILUSTRO phase II multicohort trial had three main study arms: zolbetuximab monotherapy in the third/later-line setting (Cohort 1A, n = 30); zolbetuximab with FOLFOX in the first-line setting (Cohort 2, n = 21); and zolbetuximab with pembrolizumab in the third/later-line setting (Cohort 3A, n = 3).…”
Section: Predictive Value Of Cldn 182mentioning
confidence: 60%
See 1 more Smart Citation
“…In line with the FAST trial outcomes, a recent phase II study also demonstrated interesting ORR and PFS results for the combination of zolbetuximab and chemotherapy in CLDN18.2-positive gastric or gastroesophageal adenocarcinoma [64]. The ILUSTRO phase II multicohort trial had three main study arms: zolbetuximab monotherapy in the third/later-line setting (Cohort 1A, n = 30); zolbetuximab with FOLFOX in the first-line setting (Cohort 2, n = 21); and zolbetuximab with pembrolizumab in the third/later-line setting (Cohort 3A, n = 3).…”
Section: Predictive Value Of Cldn 182mentioning
confidence: 60%
“…The authors explained that the elevation of the previous cut-off from the FAST study from 70% to 75% of tumor cells was due to the use of this new automated IHC kit. The results of these studies also favored the combination of chemotherapy with zolbetuximab compared to chemotherapy alone in gastroesophageal cancer [13,14,64].…”
Section: Predictive Value Of Cldn 182mentioning
confidence: 98%
“…These results suggest that zolbetuximab combined with chemotherapy may have superior efficacy. Additionally, the ILUSTRO trial showed that zolbetuximab plus mFOLFOX6 for first-line treatment showed positive results ( 32 ). These data support further development of zolbetuximab as a first-line treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The ILUSTRO trial is phase II non-randomized study assessing zolbetuximab efficacy (800 mg/m 2 loading dose and then at 600 mg/m 2 every 3 weeks thereafter) in patients with advanced/metastatic G/GEJ adenocarcinoma whose tumors have high (≥75% of tumor cells) or intermediate (≥50% but <75% expression of tumor cells) CLDN18.2 expression [46]. This trial comprised four cohorts.…”
Section: Clinical Trials Of Anti-cldn182 Agent For Agc or Solid Tumorsmentioning
confidence: 99%